DESIGN AND DEVELOPMENT OF AUTOMATIC REBUNG TOOLS USING VARIABLE FREQUENCY DRIVE BASED ON ARDUINO UNO - Eko Nurcahyo; Taufik Hidayat (Merdeka Malang University, 2022)
In chopping Rebung for the home industry, they still use conventional methods and lack the application of technology. This, of course, causes the productivity and quality of the home industry products to be less than optimal. Productivity is influenced by several factors, including requiring workers to be more careful so that it requires a lot of concentration, worker fatigue, which makes it less optimal in using time, and the workers' speed. Therefore, the primary control system was made an automatic Rebung chopper based on the VFD with Arduino Uno. The 3-phase induction electric motor is used as a prime mover for chopping blades and control using VFD (Variable Frequency Drive). For the critical system, use a spring and open the pressing tube's lid using a servo motor and the buzzer as a monitoring medium. The test uses VFD to adjust the rotational speed of the electric motor. The test results show that at a frequency of 20 Hz with a speed of 147.8 rpm, it produces chops with a length of 3 cm in 2 minutes 54 seconds. At a frequency of 35 Hz with a speed of 221.2 Rpm, it produces 2 cm chunks in 1 minute 53 seconds. At a frequency of 50 Hz with a speed of 260.1 Rpm, it produces 1 cm chops in 1 minute 5 seconds. If chopping is done manually, it takes 5 minutes with an average length of 2 cm